An Epidemiological Study of COVID-19 Pandemic in one Predominantly Rural District of Developing Country: A Cross-Sectional Study - Mushtaq, Beenish; Bhat, Ashfaq Ahmad; Rashid, Ashiq; Jan, Yasmeen (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: The emerging disease of COVID-19 that started from Wuhan China has now spread to more than 210 countries around the globe including India. Easy way of transmission and absence of immunity makes it highly contagious in nature. As very little data is available on various aspects of the disease, this study was taken up with the objective to generate local epidemiological data in order to provide better insight about the disease scenario prevalent in our region that will help to devise locally relevant strategies to contain the disease. Study Area: District Budgam of Kashmir Division. Materials and Methods: Cross sectional study done for a period of two month from (16th March-to 17th May) and all confirmed cases in this time frame were taken up for the study. Results: The cumulative number of cases that were reported in two months, till 17th May was 57. Out of total 10 medical blocks in the district maximum cases were reported from one block. 59.6% were reported in the age group of 20-39 years and 78.9% were males. In 71.9% cases the source of infection was contact with a positive case and 21% cases gave history of travel. Out of total 57 cases in only 12 cases the contacts turned positive and the percentage of contacts that turned positive ranged from 7% to 12 %. Conclusion: In this study estimation of the burden of disease in a district, its time distribution, block wise distribution of cases and major source of infection provide insight about the disease scenario at the local level. This study will be helpful in allocation of the limited resources that are available at the district level by health professionals. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 441-445